PERAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DALAM MEWUJUDKAN PERUSAHAAN YANG BERKELANJUTAN: ANALISIS LITERATUR TERHADAP STRATEGI & IMPLEMENTASI - Ferry Kurniawan Cahyadi; Marsillak Sautmartua Simorangkir; Rakhmad Mujoko; Sitti Rakhman (Premium Insurance Business Journal, 2025)
This study analyzes the role of Corporate Social Responsibility (CSR) in supporting corporate sustainability. CSR is not just an administrative obligation, but an important strategy to strengthen reputation and long-term competitiveness. The research method used is a qualitative approach with literature analysis from national and international journals. The results show that CSR integrated into business strategies can improve stakeholder relationships and company financial performance. The study recommends that companies integrate CSR comprehensively, develop innovative initiatives, and improve transparency and accountability in CSR reporting.